2005 Quantum Electronics and Laser Science Conference
DOI: 10.1109/qels.2005.1548790
|View full text |Cite
|
Sign up to set email alerts
|

Solitons in nonlinear media with infinite range of nonlocality: first observation of coherent elliptic solitons and vortex-ring solitons

Abstract: We present an experimental study on wave propagation in highly nonlocal optically nonlinear media, for which far-away boundary conditions significantly affect the evolution of localized beams. As an example, we set the boundary conditions to be anisotropic and demonstrate the first experimental observation of coherent elliptic solitons. Furthermore, exploiting the natural ability of such nonlinearities to eliminate azimuthal instabilities, we perform the first observation of stable vortex-ring solitons. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
102
0

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(105 citation statements)
references
References 27 publications
(15 reference statements)
3
102
0
Order By: Relevance
“…Nonlinear nonlocal media encompass a wealth of features unavailable in local Kerr-like materials, including increased stability, long-range interactions, modified spatial dispersion, etc. [4][5][6][7][8][9][10][11][12][13][14][15][16] Light beam localization in the form of optical spatial solitons was reported in nematic liquid crystals (NLC) in the year 2000 17 and was obtained by exploiting the large self-focusing response afforded by all-optical reorientation in a planar cell containing a (properly oriented) positive uniaxial fluid. The so-called "nematicons" could be generated at input powers of a few mW, 17 propagate stably and with invariant profile over several Rayleigh lengths and in two transverse dimensions, interact and mutually attract with other solitons, even at separations exceeding their transverse size, 6,18 survive collisional interactions with other nematicons or external beams or dielectric perturbations or boundaries, [19][20][21][22][23] refract or reflect when traveling across interfaces, [24][25][26][27] be deflected by electro-optically or self-induced changes in birefringent walkoff, [28][29][30][31][32] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear nonlocal media encompass a wealth of features unavailable in local Kerr-like materials, including increased stability, long-range interactions, modified spatial dispersion, etc. [4][5][6][7][8][9][10][11][12][13][14][15][16] Light beam localization in the form of optical spatial solitons was reported in nematic liquid crystals (NLC) in the year 2000 17 and was obtained by exploiting the large self-focusing response afforded by all-optical reorientation in a planar cell containing a (properly oriented) positive uniaxial fluid. The so-called "nematicons" could be generated at input powers of a few mW, 17 propagate stably and with invariant profile over several Rayleigh lengths and in two transverse dimensions, interact and mutually attract with other solitons, even at separations exceeding their transverse size, 6,18 survive collisional interactions with other nematicons or external beams or dielectric perturbations or boundaries, [19][20][21][22][23] refract or reflect when traveling across interfaces, [24][25][26][27] be deflected by electro-optically or self-induced changes in birefringent walkoff, [28][29][30][31][32] etc.…”
Section: Introductionmentioning
confidence: 99%
“…15 In the present work we study the existence and stability of PT -symmetric gap solitons in defocusing nonlocal media. Several material systems exhibit a diffusive (nonlocal) nonlinearity, particularly thermo-optic media [16][17][18][19] and nematic liquid crystals. 20,21 We extend these models to include PT -symmetric potentials.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that nonlocality can suppress modulation instability of homogeneous states [1], eliminate azimuthal instability of vortex-ring beams [2][3][4][5], prevent the collapse of self-focusing beams in media with cubic nonlinearity [6], and give rise to attraction of nonlocal dark solitons [7,8]. The stable vortex-ring solitons was first experimentally observed [9] by exploiting the natural tendency of long-range nonlocal nonlinearities to eliminate azimuthal instabilities in lead glass. It has been discussed that synthetic nonlocal nonlinearities can support the stabilization of higher-order vortices and multihump solitons [10].…”
Section: Introductionmentioning
confidence: 99%
“…Many contributions have been made in the propagation of vortex solitons with linear polarization and phase singularities [2][3][4][5][9][10][11] in nonlocal nonlinear media, described by the nonlocal nonlinear Schrödinger equation (NNLSE), which is derived from the scalar Helmholtz equation based on paraxial approximations. Whereas the scalar Helmholtz equation can be used to describe the propagation of a linearly polarized scalar beam, it is the vector Helmholtz equation that describes the propagation of the vector beams with inhomogeneous polarization.…”
Section: Introductionmentioning
confidence: 99%